Insects in outer space: assessing the effects of microgravity on edible and model insect species for spaceflight food system - Roberto Guidetti; Annette Bruun Jensen; David Copplestone; Martina Heer; Martina Heer; Paola Pittia; Lorena Rebecchi; Åsa Berggren (Frontiers in Physiology, 2025)
Insects represent an extraordinary opportunity for human nutrition in extraterrestrial conditions. Therefore, the understanding of the effects of microgravity on the biology of edible insects in space conditions is essential for their use as food. Among the mostly used ones, the house cricket Acheta domesticus, the yellow mealworm Tenebrio molitor, and the honeybee Apis mellifera have been studied in microgravity conditions. Several other insects that are not used for food have been used as model species for space experiments. Considering that currently we are 75 years from the first space missions and a multitude of experiments, the results available on the effects of microgravity in insects are scarce and fragmented. Nevertheless, some data are available, the microgravity effects are species-specific, but generally the development and behaviour of individuals are not strongly affected. The developmental and metamorphic processes seem to be able to be completed in space and the reproduction and completion of life cycle for some species are possible. Negative effects from microgravity have been seen in the immune system and in physiology of some species. The results that we have so far from disparate studies, indicate that insect species may cope in space environments and thereby be part of making future long-term exploration missions possible.